2023
DOI: 10.3389/fbioe.2023.1251947
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of titanium alloy materials with bioactive sandblasted surfaces and evaluation of osseointegration properties

Jie Wang,
Baohui Yang,
Shuai Guo
et al.

Abstract: Titanium alloys are some of the most important orthopedic implant materials currently available. However, their lack of bioactivity and osteoinductivity limits their osseointegration properties, resulting in suboptimal osseointegration between titanium alloy materials and bone interfaces. In this study, we used a novel sandblasting surface modification process to manufacture titanium alloy materials with bioactive sandblasted surfaces and systematically characterized their surface morphology and physicochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…For instance, micro-rough structures favor cell attachment, while nano-rough structures encourage gene expression, protein synthesis, and cell differentiation ( Gittens et al, 2011 ; Gittens et al, 2013 ). A variety of techniques, including plasma-sprayed ( Ferraz et al, 2001 ; Giavaresi et al, 2003 ), anodization ( Sul et al, 2002 ; Qi et al, 2021 ), sand-blasting ( Gil et al, 2021 ; Wang et al, 2023 ), and acid-etching ( Park and Davies, 2000 ; Trisi et al, 2003 ), have been employed to create biomimetic porous and rough surfaces of dental implants, and the results have demonstrated that implants with biomimetic structures would have better results for successful implant ( López-Valverde et al, 2020 ).…”
Section: Surface Modification Of Dental Implants and Biomimeticsmentioning
confidence: 99%
“…For instance, micro-rough structures favor cell attachment, while nano-rough structures encourage gene expression, protein synthesis, and cell differentiation ( Gittens et al, 2011 ; Gittens et al, 2013 ). A variety of techniques, including plasma-sprayed ( Ferraz et al, 2001 ; Giavaresi et al, 2003 ), anodization ( Sul et al, 2002 ; Qi et al, 2021 ), sand-blasting ( Gil et al, 2021 ; Wang et al, 2023 ), and acid-etching ( Park and Davies, 2000 ; Trisi et al, 2003 ), have been employed to create biomimetic porous and rough surfaces of dental implants, and the results have demonstrated that implants with biomimetic structures would have better results for successful implant ( López-Valverde et al, 2020 ).…”
Section: Surface Modification Of Dental Implants and Biomimeticsmentioning
confidence: 99%